2015
DOI: 10.1080/09168451.2014.998620
|View full text |Cite
|
Sign up to set email alerts
|

An N-terminal region of a Myb-like protein is involved in its intracellular localization and activation of a gibberellin-inducible proteinase gene in germinated rice seeds

Abstract: The expression of the gene for a proteinase (Rep1) is upregulated by gibberellins. The CAACTC regulatory element (CARE) of the Rep1 promoter is involved in the gibberellin response. We isolated a cDNA for a CARE-binding protein containing a Myb domain in its carboxyl-terminal region and designated the gene Carboxyl-terminal Myb1 (CTMyb1). This gene encodes two polypeptides of two distinctive lengths, CTMyb1L and CTMyb1S, which include or exclude 213 N-terminal amino acid residues, respectively. CTMyb1S transac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Taken together, we concluded that OsTCP21 and OsGAmyb are 224 authentic target genes of miR319. OsGAmyb is a transcription factor involved in many 225 developmental processes, such as regulating the expression of α-amylase in the aleurone layer 226 of rice seed; it also plays a role in pollen development (Liu et al 2010, Sutoh et al 2015. By 227 contrast, OsTCP21 function is related to rice responses to biotic and abiotic stresses.…”
Section: Avr1-co39mentioning
confidence: 99%
“…Taken together, we concluded that OsTCP21 and OsGAmyb are 224 authentic target genes of miR319. OsGAmyb is a transcription factor involved in many 225 developmental processes, such as regulating the expression of α-amylase in the aleurone layer 226 of rice seed; it also plays a role in pollen development (Liu et al 2010, Sutoh et al 2015. By 227 contrast, OsTCP21 function is related to rice responses to biotic and abiotic stresses.…”
Section: Avr1-co39mentioning
confidence: 99%